PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS XI SMA NEGERI 1 MATARAM TAHUN AJARAN 2023/2024 - Masayu Diska Prilliza; Irmayani Irmayani; M. Zadul Muslim (JURNAL ASIMILASI PENDIDIKAN, 2023)
The aim of this study was to apply the problem-based learning (PBL) model to improving students learning outcomes in class XI Science 7 SMA Negeri 1 Mataram for the 2023/2024 academic year. The type of research in this study was Classroom Action Research (PTK). The research subject is class XI Science 7 which consists of 37 students. Classroom action research was carried out in 3 cycles, namely pre-cycle, cycle I, and cycle II. The results obtained after carrying out classroom action research showed that there were changes to student learning outcomes. The pre-cycle showed that there were 13 students who got a score of ?80. In cycles I and II there was an increase, there were 24 students in cycle I and 32 students in cycle II. The classical completeness obtained for each cycle has increased. In cycle I obtained 64.86% in the good category. Meanwhile, in cycle II it obtained 86.49% in the very good category. Based on these data it can be concluded that the application of the PBL learning model can increase students' learning outcomes.